Is ASIO’s Corporate Governance an Oxymoron? - Rix , Mark (Journal of Law and Governance, 2015)
This paper investigates corporate governance in the Australian Security Intelligence Organisation (ASIO), Australia’s domestic intelligence agency. The paper seeks to determine and understand the extent to which ASIO’s approach to corporate governance emulates that of organisations in the wider public sector and the private sector. This examination of ASIO’s corporate governance considers the organisation’s purpose, functions and extraordinary powers focusing on the importance of secrecy to achieving its objectives. The paper will also assess whether it is appropriate to attempt to assess ASIO’s corporate governance in the same terms, and according to like standards, as are used to evaluate governance in ‘normal’ or ‘regular’ public and private sector organisations. Finally, the paper provides an overall evaluation of ASIO’s approach to corporate governance and considers how this approach affects the organisation’s treatment of its stakeholders and the extent to which it serves their interests.